2001
DOI: 10.1126/science.1058853
|View full text |Cite
|
Sign up to set email alerts
|

Energy Gaps in "Metallic" Single-Walled Carbon Nanotubes

Abstract: Metallic single-walled carbon nanotubes have been proposed to be good one-dimensional conductors. However, the finite curvature of the graphene sheet that forms the nanotubes and the broken symmetry due to the local environment may modify their electronic properties. We used low-temperature atomically resolved scanning tunneling microscopy to investigate zigzag and armchair nanotubes, both thought to be metallic. "Metallic" zigzag nanotubes were found to have energy gaps with magnitudes that depend inversely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
492
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 705 publications
(549 citation statements)
references
References 20 publications
52
492
1
4
Order By: Relevance
“…[22][23][24][25] It is now known that SWNTs can behave as metals, semiconductors, or small band-gap semiconductors, [26][27][28] depending upon their diameter and chirality. 29 Electronic transitions between the energy bands of SWNTs ( Figure 2) can be observed by standard spectroscopic techniques.…”
Section: Preparation and Solid State Propertiesmentioning
confidence: 99%
“…[22][23][24][25] It is now known that SWNTs can behave as metals, semiconductors, or small band-gap semiconductors, [26][27][28] depending upon their diameter and chirality. 29 Electronic transitions between the energy bands of SWNTs ( Figure 2) can be observed by standard spectroscopic techniques.…”
Section: Preparation and Solid State Propertiesmentioning
confidence: 99%
“…Depending on the diameter and chirality, the tubes may have electrochemical properties similar to metals (Ouyang et al 2001), or as semiconductors (Itkis et al 2002). Their variability in electrochemical behavior makes them attractive to microelectronic applications (Avouris 2007).…”
Section: Introduction Carbon Nanotubesmentioning
confidence: 99%
“…The obtained C-C bond length is 1.34Å, which shows reasonable agreement with our recent XRD result. 36 Thus, 13 C enriched NMR can be applied for the determination of the C-C bond length of SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…The SQUID measurements indicated that the amount of ferromagnetic impurities in the purified sample was two orders of magnitude smaller than in pristine material. 13 C NMR measurements were performed under a magnetic field of 9.4 Tesla. The nuclear spin-lattice relaxation rate T −1 1 was determined by a saturation recovery method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation